2014
DOI: 10.1186/1477-7827-12-36
|View full text |Cite
|
Sign up to set email alerts
|

Kinase insert domain receptor/vascular endothelial growth factor receptor 2 (KDR) genetic variation is associated with ovarian hyperstimulation syndrome

Abstract: BackgroundThe objective of this investigation was to determine if kinase insert domain/vascular endothelial growth factor receptor 2 (KDR/VEGFR2) genetic variation was associated with the development of ovarian hyperstimulation syndrome (OHSS) in patients undergoing controlled ovarian hyperstimulation (COH).MethodsThis was a case–control study of 174 patients who underwent controlled ovarian stimulation. Patient blood samples were genotyped for single nucleotide polymorphisms (SNPs) spanning the KDR locus. OHS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…For example, Jang et al found KDR SNPs (1192G>A) could reduce the risk of colorectal cancer in Koreans [33]. KDR variation (rs2305945, G/T) can lead to ovarian hyperstimulation syndrome in Travis's research [34]. Zheng et al discovered KDR polymorphisms with vascular malformation [35].…”
Section: Introductionmentioning
confidence: 97%
“…For example, Jang et al found KDR SNPs (1192G>A) could reduce the risk of colorectal cancer in Koreans [33]. KDR variation (rs2305945, G/T) can lead to ovarian hyperstimulation syndrome in Travis's research [34]. Zheng et al discovered KDR polymorphisms with vascular malformation [35].…”
Section: Introductionmentioning
confidence: 97%
“…Although this SNP is located within a non-coding region of VEGFR-2 , there are data suggesting it is of clinical interest. Indeed, previous data has reported that rs2305945 is associated with differential response to VEGF inhibitors in age-related macular degeneration and also protective against ovarian hyperstimulation syndrome [ 29 , 30 ]. The latter is of particular relevance here given the physiological importance of VEGF to follicular cysts formation and the plethora of trials that have demonstrated the clinical activity of VEGF inhibitors in ovarian cancer, irrespective of the platinum/progression-free interval.…”
Section: Discussionmentioning
confidence: 99%